Financial Reporting in the Perception of Heptagon Fraud Theory - Noval Adib; Meilenia Rahma; Areta Widya (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the effect of fraud heptagon consisting of seven elements, namely pressure, rationalization, opportunity, arrogance, ability or competence, culture, and religiosity on financial statement fraud in SMEs employees in Indonesia. This research method is quantitative with a questionnaire. Respondents who were successfully collected were 250 who were SMEs employees in the finance department in Indonesia. Data were collected through questionnaire distribution and then processed using a statistical application, namely SPSS. The results obtained from the processing were pressure, rationalization, opportunity, arrogance, ability or competence, and culture had an effect on financial statement fraud. However, this study found that religiosity had no effect on financial statement fraud. The practical contribution of the study can be the implementation of the fraud heptagon theory in financial statement fraud and a practical contribution to all State-owned enterprises (SMEs) management in Indonesia, namely it can be an evaluation of how important pressure, rationalization, opportunity, arrogance, ability or competence, and culture are in preventing fraud.